Implementation Teaching Material Integrated Spiritual Values with Discovery Learning Model to Improve Learning Outcomes - Rizky Andini; Ayi Darmana (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This study examines the effect of integrating spiritual values into chemistry teaching materials through the Discovery Learning model on students’ learning outcomes and spiritual attitudes at SMA Negeri 5 Medan. Using a quasi-experimental design, two grade XI classes were selected, namely XI-4 (experimental) and XI-8 (control). The experimental class received spiritually integrated materials, while the control class used a standard handbook. Data were collected through learning outcomes tests and spiritual attitude questionnaires. Findings showed significant improvements in the experimental group’s post-test scores and spiritual attitudes. Statistical analysis using independent and paired sample t-tests yielded significance values of 0.000 (≤ 0.05). A Pearson correlation test showed a strong positive correlation (r = 0.644, R² = 0.414), indicating that higher spiritual attitudes are associated with better academic performance.